2012
DOI: 10.1016/j.apmr.2011.07.197
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Scores of a Chinese Version of the Frenchay Activities Index

Abstract: Objective-To develop a Chinese version of the Frenchay Activities Index (FAI-C) and evaluate the reliability and validity of its scores. Design-A two-week test-retest study.Setting-Chinese community in Vancouver, BC, Canada.Participants-Data were collected using a convenience sample of Chinese immigrants living in Vancouver, BC, Canada. Of the 73 participants, data from 66 participants were included in the analysis. The total sample included two subsamples: community dwelling (n = 32), and assisted living (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…This divergence may have occurred because individuals in the latter studies were evaluated one year after stroke and the second inter-rater assessment occurred seven to 20 days after the first evaluation. Thus, the results could have been influenced by recall bias or health changes occurring during the period between tests 20 . The present study demonstrated a significant correlation, although weak, using Spearman's test, between the FAI and NIHSS scores in the acute phase, possibly due to the additional association of other variables with the outcome NIHSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…This divergence may have occurred because individuals in the latter studies were evaluated one year after stroke and the second inter-rater assessment occurred seven to 20 days after the first evaluation. Thus, the results could have been influenced by recall bias or health changes occurring during the period between tests 20 . The present study demonstrated a significant correlation, although weak, using Spearman's test, between the FAI and NIHSS scores in the acute phase, possibly due to the additional association of other variables with the outcome NIHSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 19 studies were included in this systematic review. 19---37 The following six self-report measures of physical activity levels were identified, three of them in two different versions: 19,21,24 The Activity Card Sort (ACS and ACS-Hong Kong version), 19,34 Coded Activity Diary, 35 Frenchay Activities Index (FAI and FAI-chinese version), 23---32,36,37 Human Activity Profile (HAP), 33 Multimedia Activity Recall for Children and Adults (MARCA), 22 and the Nottingham Leisure Questionnaire (original and short versions). 20,21 These measures are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated internal consistency: two showed ''poor'', ACS 19 and FAI, 32 and one ''good'', FAI, 25 methodological quality. Reliability was analyzed in 11 studies: three showed ''poor'', FAI 23,36 and Nottingham Leisure Questionnaire, 20 five '' fair'', FAI, 27---29 MARCA 22 and Nottingham Leisure Questionnaire, 21 and three ''good'', ACS 19 and FAI, 24,26 methodological quality. Measurement error was described in one study with ''good'', FAI, 26 methodological quality.…”
Section: Assessment Of the Methodsological Quality Using The Cosmin Tamentioning
confidence: 99%
“…International University (No. [17][18][19][20][21][22]. The participants had the right to withdraw from the study at any time for any reason.…”
Section: Ethics Statementmentioning
confidence: 99%
“…The FAI was originally developed to assess the status of instrumental activities of daily living (IADL) for stroke patients [12], and many studies have been conducted with patients with various illnesses and injuries, including lower limb amputation [13], multiple sclerosis [14], and spinal cord injury [15], and it has also been applied to the general elderly population [16]. The validity and reliability of various country-specific translations of the scales have been confirmed, including, for the Japanese, Chinese, and Korean versions [17] [18] [19]. Several studies on factor analysis of FAI have been reported.…”
Section: Introductionmentioning
confidence: 98%